Emotional Demands at Work and the Risk of Clinical Depression: A Longitudinal Study in the Danish Public Sector. Issue 10 (October 2016) - Vammen, Marianne Agergaard; Mikkelsen, Sigurd; Hansen, Åse Marie; Bonde, Jens Peter; Grynderup, Matias B.; Kolstad, Henrik; Kærlev, Linda; Mors, Ole; Rugulies, Reiner; Thomsen, Jane Fr⊘lund
Abstract : Objective: This study is a 2-year follow-up study of different dimensions of work-related emotional demands as a predictor for clinical depression. Methods: In a two-wave study, 3224 (72%) public employees from 474 work-units participated twice by filling in questionnaires. Sixty-two cases of clinical depression were diagnosed. Emotional demands were examined as perceived and content-related emotional demands, individually reported and work-unit based. Support, meaningful work, and enrichment were considered as potential effect modifiers. Results: Individually reported perceived emotional demands predicted depression (odds ratio: 1.40; 95% confidence intervals: 1.02 to 1.92). The work-unit based odds ratio was in the same direction, though not significant. Content-related emotional demands did not predict depression. Support, meaningful work, and enrichment did not modify the results. Conclusions: The personal perception of emotional demands was a risk factor for clinical depression but specific emotionally demanding work tasks were not.